1987
DOI: 10.1099/0022-1317-68-11-2769
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Monoclonal Antibodies to Simian Virus 5 and Their Use in Revealing Antigenic Differences between Human, Canine and Simian Isolates

Abstract: SUMMARYHybridomas secreting monoclonal antibodies to simian virus 5 (SV5) were obtained following immunization of mice with purified preparations of a human isolate (LN) of SV5. Immune precipitation studies showed that these monoclonal antibodies had specificities for the haemagglutinin-neuraminidase (HN), fusion (F), nucleo-, matrix and phospho-(P) proteins of SV5. By use of a radioimmune competition assay the monoclonal antibodies to the HN protein were assigned to four groups, members of which recognized di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 32 publications
7
140
0
Order By: Relevance
“…Parainfluenza viruses are classified in the family Paramyxoviridae, subfamily Paramyxovirinae. CPIV is antigenically similar to the simian virus 5 (SV5) and to porcine, bovine, ovine and feline parainfluenza viruses [1,127]. Sequence analysis of the fusion protein-encoding gene has revealed that CPIV has 99.3% nucleotide similarity to porcine parainfluenza virus, 98.5% to SV5 and 59.5% nt to human parainfluenza virus 2 [111].…”
Section: Canine Parainfluenzavirusmentioning
confidence: 99%
“…Parainfluenza viruses are classified in the family Paramyxoviridae, subfamily Paramyxovirinae. CPIV is antigenically similar to the simian virus 5 (SV5) and to porcine, bovine, ovine and feline parainfluenza viruses [1,127]. Sequence analysis of the fusion protein-encoding gene has revealed that CPIV has 99.3% nucleotide similarity to porcine parainfluenza virus, 98.5% to SV5 and 59.5% nt to human parainfluenza virus 2 [111].…”
Section: Canine Parainfluenzavirusmentioning
confidence: 99%
“…The procedures used for the isolation of MAbs to PF-2 were the same as those described in detail for the production of MAbs to SV5 (Randall et al, 1987). The nomenclature system for the PF-2 MAbs was similar to that used for the SV5 MAbs i.e.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…1.5 mg/1). At the end of the labelling period the medium was harvested for virus purification and the cells were used to make soluble antigen extracts for the immune precipitation reactions, as described in detail elsewhere (Randall et al, 1987). The proteins present in the immune precipitates and in the partially purified virus preparations were analysed by SDS-PAGE and autoradiography (Randall et al, 1987).…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations